Grape-leaf extract attenuates alcohol-induced liver injury via interference with NF-[kappa]B signaling pathway - Amen, Yhiya; Sherif, Asmaa E.; Shawky, Noha M.; Abdelrahman, Rehab S.; Wink, Michael; Sobeh, Mansour (Biomolecules, 2020)
Grape (Vitis vinifera) leaf extracts (GLEs) are known to be rich in phenolic compounds that exert potent antioxidant effects. Given the vulnerability of the liver to oxidative damage, antioxidants have been proposed as therapeutic agents and coadjuvant drugs to ameliorate liver pathologies. The current study was designed to characterize secondary metabolites and investigate the hepatoprotective effects of GLE and its underlying mechanisms. The secondary metabolites were profiled using HPLC–PDA–ESI-MS, and forty-five compounds were tentatively identified. In experimental in vivo design, liver injury was induced by oral administration of high doses of ethanol (EtOH) for 12 days to male Sprague Dawley rats that were split into five different groups. Blood samples and livers were then collected, and used for various biochemical, immunohistochemical, and histopathological analyses. Results showed that GLE-attenuated liver injury and promoted marked hepatic antioxidant effects, in addition to suppressing the increased heat-shock protein-70 expression. Moreover, GLE suppressed EtOH-induced expression of nuclear factor-κB (NF-κB) p65 subunit and proinflammatory cytokine tumor necrosis factor-α. Caspase-3 and survivin were enhanced by EtOH intake and suppressed by GLE intake. Finally, EtOH-induced histopathological changes in liver sections were markedly normalized by GLE. In conclusion, our results suggested that GLE interferes with NF-κB signaling and induces antioxidant effects, which both play a role in attenuating apoptosis and associated liver injury in a model of EtOH-induced liver damage in rats.
Im Titel ist [kappa] als griechischer Buchstabe dargestellt
Gesehen am 20.07.2020